Toward an Identity-Based Integration Strategy: Hybrid Pastoral Practice by a Korean Chaplain Intern in a U.S. Hospital - Kim, Miyoung (Pastoral psychology, 2025)
This study explores the intercultural tensions and identity shifts experienced by a Korean chaplain intern during clinical pastoral education (CPE) at a U.S. hospital. Employing autoethnography as a qualitative method, this research narratively examines how identity-based integration strategies can extend beyond behavioral adaptation toward narrative reconstruction and ethical transformation in caregiving practices. The theoretical framework integrates Homi Bhabha’s postcolonial cultural theory, particularly the concepts of mimicry, ambivalence, and hybridity, with Paul Ricoeur’s notion of narrative identity. Through this framework, the study expands Berry’s acculturation strategy of "integration" into an identity-based integration strategy, shedding light on hybrid pastoral practice. The findings yielded four key themes: (1) awareness of cultural difference and self-reflection, (2) mimicry and cultural reconstruction, (3) ambivalence and identity tension, and (4) hybrid identity and integrative pastoral practice. These themes demonstrate how identity is narratively shaped at cultural boundaries and realized through ethical caregiving practice. Ultimately, this study highlights the agency of minority care providers as ethical subjects who reconstruct identity and practice in intercultural settings. It offers a conceptual and practical framework for "identity-based integration strategy" within multicultural pastoral care contexts.